2005
DOI: 10.4161/org.2.1.1726
|View full text |Cite
|
Sign up to set email alerts
|

Low Ambient O2Enhances Ureteric Bud Branching In Vitro

Abstract: Previously published online as an Organogenesis E-publication: http://www.landesbioscience.com/journals/organogenesis/abstract.php?id=1726 KEY WORDSmetanephroi, embryogenesis, fibroblast growth factor, vascular endothelial growth factor ACKNOWLEDGEMENTS T. Akimoto and E. Kusano were supported by in part by a Grant-in-Aid for Scientific Research from the Ministry of Education, and Grants from Jin-Kenkyu-Kai. M.R. Hammerman was supported by grant DK 63379 from NIDDK. Research Paper Low Ambient O 2 Enhances Urete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Previous research has shown that low ambient O 2 enhances ureteric bud branching in vitro [15], but the detailed mechanism is unknown. We investigated the effect of hypoxia on kidney development.…”
Section: Introductionmentioning
confidence: 96%
“…Previous research has shown that low ambient O 2 enhances ureteric bud branching in vitro [15], but the detailed mechanism is unknown. We investigated the effect of hypoxia on kidney development.…”
Section: Introductionmentioning
confidence: 96%
“…The previously described 2005 study showed that VEGF and FGF2 played a role in UB branching in both oxygen tension conditions [48]. The 2015 study furthered this, demonstrating that hypoxic HIF activation increases paracrine VEGFA signaling to inhibit nephrogenesis but enhance tubulogenesis [50].…”
Section: Oxygen Tension and Ureteric Branchingmentioning
confidence: 82%
“…A 2005 study demonstrated that cultured E12 mouse kidney explants grown in 5% O 2 had more extensive ureteric branching than those cultured in 20% O 2 [48] (Table 1). Furthermore, E13 rat kidney explants cultured in 5% O 2 for 96 hours had significantly more UB branching than kidneys cultured in 21% O 2 [49].…”
Section: Oxygen Tension and Ureteric Branchingmentioning
confidence: 99%
“…It has been reported that foetal hypoxia decreases nephron numbers and kidney weight [ 2 ]. However, it has been shown that hypoxia stimulates ureteric bud branching in vitro [ 3 ]. In this regard, an appropriately low O 2 tension is necessary for embryonic development.…”
Section: Introductionmentioning
confidence: 99%